PENEGAKAN HUKUM TERHADAP OKNUM ANGGOTA KEPOLISIAN PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA DI WILAYAH HUKUM KEPOLISIAN RESOR ROKAN HULU - Nabilla Khaernas; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Narcotics abuse with perpetrators who are members of the Rokan Hulu Resort Police isincreasing every year. In 2019 as many as 3 people, 2020 as many as 5 people and 2021 as many as8 people. One of them is the case in Decision Number 286/Pid.Sus/2019/PNPrp, the sanctionimposed on the perpetrator is ten months' imprisonment. This shows that there is a contradiction inthe nature and duties of the police, which should enforce the law itself, as well as the provision oflighter sanctions compared to ordinary people who commit similar crimes.The type of research used in writing this law is sociological legal research. Meanwhile, ifviewed from the nature of this research is descriptive. This research was conducted at the RokanHulu Police.The results of this study are law enforcement against the perpetrators of the Crime ofNarcotics Abuse carried out by unscrupulous members of the police in the jurisdiction of the RokanHulu Resort Police consisting of the investigation and investigation stage, the general court stage,the code of ethics trial stage and dishonorable discharge. However, the defendant was not dismissedfrom the police force and was given the opportunity to improve himself and still received 2/3 of hissalary during his detention. Obstacles in carrying out law enforcement against unscrupulousmembers of the police who are perpetrators of criminal acts of narcotics abuse in the jurisdiction ofthe Rokan Hulu Resort Police, namely the legal factor, namely changes in regulations governing thePolice Professional Code of Ethics that always occur and have multiple interpretations, theindividual factor of Polri members is the accused member of the police already very aware of thesituation and circumstances in the office, looking for opportunities to use drugs, environmentalfactors, namely the association of police officers outside the service have a negative effect on him sothat things can happen that harm him by abusing narcotics, lack of public participation in providinginformation and complaints, and the availability of drugs. Efforts made by the Rokan Hulu ResortPolice to overcome obstacles in carrying out law enforcement against unscrupulous members of thepolice who commit narcotics abuse crimes within the jurisdiction of the Rokan Hulu Resort Police,namely more intense supervision, routine raids, surprise inspections and urine tests, outreachactivities to community and take decisive action.Keywords: Law Enforcement, Police Personnel, Narcotics, Criminal act, Rokan Hulu ResortPolice